Laboratory validation of patient-specific templating for total knee arthroplasty - Mahmoud A. Hafez; Arne Jansen; Frank Portheine; Branislav Jaramaz (Scientific Reports)
Abstract Patient-specific templating (PST), which is a sister procedure to patient-specific instrumentation (PSI) but hospital-based, is relatively less complex and less expensive than robotics and navigation. However, there are some concerns about the PST including the process of preoperative planning, 3D printing and material, positioning of PST intraoperatively, availability, and clinical value. The purpose of this study was to validate the technical accuracy and reliability of the PST technique in the lab and to report the outcomes of clinical application. To test the reliability of the PST technique, five observers positioned the PST templates five times over the distal femur and proximal tibial whilst a navigation system was used to measure the level of bone cutting, coronal and sagittal alignment, and rotation in both femur and tibia. The mean alignment error in all planes was 0.67° (maximum 2.5°). Concerning the bone (femoral and tibial) cutting, the mean error was 0.32 mm (maximum 1 mm). The qualitative and quantitative analysis showed an overall agreement between observers (p < 0.05). The laboratory part of this study showed that the positioning of the PST over the proximal tibia and distal femur during TKA is reliable. There were statistically insignificant intraobserver and interobserver variations.